Transient Hypertension after Spinal Cord Injury Leads to Cerebrovascular Endothelial Dysfunction and Fibrosis - Aaron A. Phillips; Nusrat Matin; Mengyao Jia; Jordan W. Squair; Aaron Monga; Mei Zheng; Rahul Sachdeva; Andrew Yung; Shea Hocaloski; Stacy Elliott; Piotr Kozłowski; Anne M. Dorrance; et al. (2017)
We aimed to create a clinically relevant pre-clinical model of transient hypertension, and then evaluate the pathophysiological cerebrovascular processes resulting from this novel stimulus, which has recently been epidemiologically linked to cerebrovascular disease. We first developed a clinically relevant model of transient hypertension, secondary to induced autonomic dysreflexia after spinal cord injury and demonstrated that in both patients and rats, this stimulus leads to drastic acute cerebral hyperperfusion. For this, iatrogenic urodynamic filling/penile vibrostimulation was completed while measuring beat-by-beat blood pressure and cerebral blood flow (CBF) in patients. We then developed a rodent model mimicking the clinical reality by performing colorectal distention (to induce autonomic dysreflexia) using pre-clinical beat-by-beat blood pressure and CBF assessments. We then performed colorectal distension in rats for four weeks (6x/day) to evaluate the long-term cerebrovascular consequences of transient hypertension. Outcome measures included middle cerebral artery endothelial function, remodeling, profibrosis and perivascular innervation; measured via pressure myography, immunohistochemistry, molecular biology, and magnetic resonance imaging. Our model demonstrates that chronic repetitive cerebral hyperperfusion secondary to transient hypertension because of autonomic dysreflexia: (1) impairs cerebrovascular endothelial function; (2) leads to profibrotic cerebrovascular stiffening characterized by reduced distensibility and increased collagen deposition; and (3) reduces perivascular sympathetic cerebrovascular innervation. These changes did not occur concurrent to hallmark cerebrovascular changes from chronic steady-state hypertension, such as hypertrophic inward remodeling, or reduced CBF. Chronic exposure to repetitive transient hypertension after spinal cord injury leads to diverse cerebrovascular impairment that appears to be unique pathophysiology compared with steady-state hypertension in non-spinal cord injured models.